2021
DOI: 10.1371/journal.pone.0257059
|View full text |Cite
|
Sign up to set email alerts
|

Virologic outcomes of people living with human immunodeficiency virus who started antiretroviral treatment on the same-day of diagnosis in Ethiopia: A multicenter observational study

Abstract: Introduction There have been tremendous achievements in scaling-up antiretroviral therapy (ART) for treatment of human immunodeficiency virus (HIV), following universal “test and treat” policy implementation in low- and middle-income countries. However, its effects on virologic outcomes is not yet well investigated. We compared low viral load status in people living with HIV between those who were initiated on ART on the same-day and after 7 days of being diagnosed with HIV infection. Methods We conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our ART adherence results correlate with the lower viral suppression we found among same-day group in our previous publication that focused on virologic outcomes. 35 Viral load measurement has been used as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ART adherence results correlate with the lower viral suppression we found among same-day group in our previous publication that focused on virologic outcomes. 35 Viral load measurement has been used as…”
Section: Discussionmentioning
confidence: 99%
“…Our ART adherence results correlate with the lower viral suppression we found among same-day group in our previous publication that focused on virologic outcomes. 35 Viral load measurement has been used as another way of assessing ART adherence 36 — sometimes considered as the gold standard for monitoring ART adherence. 37…”
Section: Discussionmentioning
confidence: 99%
“…The HPTN 052 trial in nine African countries clearly showed that early initiation of ART with CD4 counts between 350 and 550 cells /mm 3 facilitated the faster achievement of viral load suppression and reduced HIV transmission by approximately 96% compared to late ART initiation with CD4 count < 250 cells /mm 3 [9]. Observational studies conducted in South Africa [10], Eswatini [11] and Ethiopia [12], which compared early treatment with standard care, reported similar results. Moreover, if ART is initiated immediately, the cost of hospitalization may be minimized in resource-poor and HIV-prone prevalence countries [13,14].…”
Section: Introductionmentioning
confidence: 91%